Implementasi Knowledge Management System Dalam Upaya Peningkatan Pengetahuan Sumber Daya Manusia Dengan Metode Seci - Edy Siswanto (Jurnal Manajemen Informatika & Teknologi, 2021)
APF is an international textile company that focuses on producing textile yarns located in Kendal district, Semarang city. This study aims to create a system using knowledge storage and management that is useful for sharing HR knowledge and to increase the speed of all handling conflicts. . The author reveals that using the existence of news knowledge management can facilitate organization and provide information and knowledge for the company, it can also increase the speed of handling conflicts that occur in the company